Anaerobic digestion of Fischer-Tropsch reaction water : submerged membrane anaerobic reactor design, performance evaluation & modeling - Van Zyl, Pierrie Jakobus (Department of Civil Engineering, 2014)
Includes abstract. Includes bibliographical references (p. 209-217).